Relation of myofibril fragmentation to textural and chemical parameters of aged pork Longissimus dorsi - Dejan DOŠLER; Tomaž POLAK; Božidar ŽLENDER; Lea GAŠPERLIN (Acta Agriculturae Slovenica)
The relation of myofibrilar fragmentation (length of myofibrilar fragments, myofibrilar fragmentation index) to textural (Warner-Bratzler share force) and chemical parameters (non-protein nitrogen changes) of pork Longisimus dorsi muscles (acquired 24 h post mortem, normal meat quality) were investigated over a 16-day ageing period at 2 °C (± 1 °C). Ageing time significantly affected all parameters at the 1% level or less. The pH value for 16-day aged samples was slightly higher; the average values being 5.61 for nonaged and 5.67 for aged samples. Length of myofibrilar fragments being in average the highest (73 mm) for nonaged samples, and the lowest (15.7 mm and 12.4 mm) for 11 and 16 days aged ones. Myofibrilar fragmentation index increases significantly with storage: for nonaged samples below 30, after a 2-day ageing about 50, and after 5-day ageing 63.7 (determined as described by Olson et al., 1976), or after 11-day ageing 56.9 (determined as described by Hopkins et al., 2004) Indexes for Hopkins procedure were about 7% lower (P ≤ 0.001) compared to those for Olson procedure. Non-protein nitrogen after 11 and 16 days of storage was higher (10.78% and 10.93% of total nitrogen) compared to the nonaged pork (9.39% of total nitrogen). Warner-Bratzler share force was markedly affected by 16-day ageing (nonaged 51.3 N, 16 days 29.2 N). On the basis of instrumentally measured texture differences in thermally treated aged pork we concluded that myofibrilar fragmentation index was a suitable proteolysis rate pointer already from the second day on. The increase in non-protein nitrogen content indicates a release of free amino acids; so, it is a suitable measure of proteolysis after 5 days of ageing.